Cholesterol regulation of receptor-interacting protein 140 via microRNA-33 in inflammatory cytokine production - Ho, Ping-Chih (Federation of American Societies for Experimental Biology, 2011)
Receptor interacting protein 140 (RIP140) is a nuclear receptor coregulator that affects a wide spectrum of biological processes. It is unclear whether and how the expression level of RIP140 can be modulated and whether RIP140 is involved in inflammatory diseases. Here, we examine how intracellular cholesterol regulates RIP140 expression, and we evaluate the effect of RIP140 expression on macrophage proinflammatory potential. Macrophages treated with modified low-density lipoprotein express higher RIP140 mRNA and protein levels. Consistently, simvastatin reduces RIP140 levels, which can be reversed by mevalonate. Moreover, a high-fat diet elevates RIP140 but lowers miR-33 levels in peritoneal macrophages, and increases the production of IL-1β and TNF-α in macrophages. Mechanistically, miR-33 targets RIP140 mRNA by recognizing its target located in a highly conserved sequence of the 3′-untranslated region (3′-UTR) of RIP140 mRNA. Consequentially, miR-33 reduces RIP140 coactivator activity for NF-κB, which is supported by the reduction in NF-κB reporter activity and the inflammatory potential in macrophages. This study uncovers a cholesterol-miR-33-RIP140 regulatory pathway that modulates the proinflammatory potential in macrophages in response to an alteration in the intracellular cholesterol status, and identifies RIP140 as a direct target of miR-33 that mediates simvastatin-triggered anti-inflammation.—Ho, P.-C.; Chang, K.-C., Chuang, Y.-S., Wei, L.-N. Cholesterol regulation of receptor-interacting protein 140 via microRNA-33 in inflammatory cytokine production.